Training load and well-being status variations of elite futsal players across a full season: Comparisons between normal and congested weeks - Clemente, F. M.; Martinho, R.; Calvete, F.; Mendes, B. (Physiology & Behavior, 2019)
The aim of this study was two-fold: (i) to analyze the variations of internal load (IL) and well-being between normal and congested weeks in professional futsal (also known as indoor soccer) players and (ii) to analyze variations in training days (MD-1, MD-2 and MD-3 [matchday -1, -2, and -3, respectively]) within weeks. Twenty male professional futsal players (age: 27.8 ± 5.7 years old; height: 173.8 ± 5.6?cm; weight: 71.5 ± 7.9?kg) that participated in the first futsal league of Portugal were monitored in all training sessions and matches during a full season. Session ratings of perceived exertion and a Hooper questionnaire (to measure muscle soreness, stress, fatigue, and sleep) were used to monitor the IL and well-being, respectively. Almost certain large decreases in IL during congested weeks in training session MD-3 were observed (-27.7%, [-35.8;-18.6]). Likely moderate decreases in IL during congested weeks in the MD-2 session were also verified (-9.9%, [-17.2;-2.0]). Regarding muscle soreness, almost certain large decreases were found during congested weeks on MD-3 (-21.2%, [-30.0;-11.3]) and MD-1 (-17.3%, [-26.6;-6.9]). Similar evidence was found for fatigue level, as almost certain large decreases were observed during congested weeks on MD-3 (-23.5%, [-32.9;-12.7]) and MD-1 (-16.6%, [-24.8;-7.4]). Within-week changes during normal weeks revealed almost certain large increases in internal load on MD-2 (93.4%, [78.6;109.3]) and MD-3 (106.7%, [88.2;127.0]) in comparison with MD-1. Also, during congested weeks, almost certain large increases of internal load were observed on MD-2 (77.2%, [53.4;104.7]) and MD-3 (65.7%, [42.8;92.3]) in comparison with MD-1. The major findings of this study revealed meaningful increases of IL, muscle soreness, and fatigue in normal weeks in comparison to congested ones. Within-week changes were also observed, with the greatest loads being observed on MD-3 during normal weeks and on MD-2 during congested weeks.